AN ERROR ANALYSIS OF NARRATIVE TEXT WRITTEN BY STUDENTS OF ENGLISH EDUCATION DEPARTMENT - Deni Deni; TMA. Kristanto (Universitas Sarjanawiyata Tamansiswa, 2017)
Therefore, the objectives of the article are:(1) to describe the kinds of errors made by the third semester students of the English Language Education Study Program in writing narrative text and (2) to find out the sources of the errors made by the third semester students of The English Language Education Study Program in writing narrative text. This article is classified into discourse analysis. To analyze the data, the researchers used Dulay et al’s theory namely surface strategy taxonomy, communicative effect taxonomy and Brown’ theory namely interlingual transfer and intralingual transfer. The data were sentences on narrative texs containing errors taken from weekly journal of the third semester students of the English Language Education Study Program of Sarjanawiyata Tamansiswa University in academic year 2015/2016. There were 152 data containing omission, 98 data containing addition, 432 data containing misformation, and 17 data containing misordering. Meanwhile, the sources of error that the researchers found are 16 errors caused by interlingual transfer and 276 caused by intralingual transfer.